A Stranger in Berlin: On Joseph Roth's Berlin Discourse - Sabine Hake (Studies in 20th & 21st Century Literature, 2004)
As the quintessential urbanite, Joseph Roth continues to be extremely relevant to ongoing public debates on Berlin's identity as the new center of a multicultural society and architecture of postmodern urbanity…
Keywords: urbanite; Joseph Roth; urban; Berlin& #x27; s identity; Berlin; identity; multicultural society; postmodern